Learning with the Internet of Things - Moreira, F. T. (2020)
An IoT system was developed to allow obtaining data on humidity, temperature and air pressure, soil moisture and pH, ultraviolet index, and gases. Complementarily to the development of the device, a visual guide was created to facilitate the construction of the same procedure by teachers and students, even if they do not have knowledge about the use of IoT technologies. Along with the building guides, didactic guides were also developed to be used in activities related to learning of topics on physics, chemistry, natural sciences, geography, and mathematics that take advantage of data obtained from the developed devices. In parallel, a wiki of open data feeds, provided by several international institutions, relevant to Portuguese curricula contents, was also created. These guides have been validated by experts and are now being assessed in a pilot study involving 97 students (all from 7th grade) from Aveiro’s schools (Portugal) and 10 teachers from different disciplinary areas. This paper will provide a discussion of the power of IoT in Education, a description of the materials developed and their pedagogical rationale, and, also, the preliminary results from the pilot study.